Perancangan Sistem Reservasi Online Untuk Lia Perawatan Kulit Berbasis Website Menggunakan Framework Express.Js - Prasetio, Alvin; Mansyuri, Umar; Arief, Rahadian (Universitas Pakuan, 2025)
DESIGNING AN ONLINE RESERVATION SYSTEM FOR WEBSITE-BASED SKINCARE LILIES USING EXPRESS.JS FRAMEWORKThe need for fast and practical services is very important, including in the beauty service sector. Lia Skin Care still uses a manual reservation system that causes various obstacles, such as long queues, recording errors, and lack of flexibility for customers. This research aims to design a website-based online reservation system that makes it easier for customers to order services and helps salons manage schedules and data more efficiently. The system development method used in this study is Waterfall, with the stages of needs analysis, system design, implementation, testing, and maintenance. The results of the study show that the proposed system can minimize recording errors, make it easier for customers to choose schedules independently, and improve the operational efficiency of Lia Kulit Care. This system also supports digital recording of customer data, making it easier to process services and decision-making. In conclusion, the web-based online reservation system developed is able to provide an effective solution to the problem of manual reservations and supports digital transformation in beauty services.